Sustained virological response following chronic hepatitis C treatment is associated with improvement in insulin resistance. Issue 6 (9th June 2013) - Chan, C. H. Y.; Hansen, R. D.; Gilliver, R. S.; Jones, B. E.
Abstract Background Insulin resistance (IR) is a key factor in the development of hepatic steatosis and fibrosis in chronic hepatitis C virus infection. Little is known about the impact of viral clearance on IR. Aim The aim of this study was to determine the impact of viral clearance on IR. Methods Eighty‐six patients treated according to standard clinical practice at an Australian teaching hospital between 2003 and 2007 were prospectively studied. Demographic, biochemical and histological data were collected. Results The mean pretreatment homeostatic model assessment–IR (HOMA‐IR) was similar in the sustained virological response (SVR) and non‐SVR groups (2.7 ± 0.5 and 2.8 ± 0.4, respectively), and both values were consistent with significant IR. There was a significant improvement in HOMA‐IR (from 3.0 ± 1.0 to 2.2 ± 0.5, P = 0.04) at the end of treatment in the SVR group only. This trended towards significance at 6 months post‐treatment. Multiple regression analysis found improvement in both gamma‐glutamyl transpeptidase and alanine aminotransferase predicted improvement in HOMA‐IR when controlled for other potential factors (P = 0.01). Conclusions Hepatitis C virus clearance is associated with improvement in IR. Although baseline hepatic fibrosis is a predictor of IR, changes in IR appear to be independent of changes in liver fibrosis. Treatment‐related improvement in gamma‐glutamyl transpeptidase and alanine aminotransferase seen with improved IR may be a possible marker of reduction of hepatic oxidative stress.